Psychologie de l'orientation, théorie de l'action et récits de vie - Francequin, Ginette (Canadian Journal of Counselling and Psychotherapy, 2007)
This article describes new practices for counselling adolescents in the secondary school context using a narrative methodology. The interactive approaches favoured by groups based on reflections on writings or drawings are explained. Within a group of volunteers, discussion helps individual members to develop hypotheses about their backgrounds and narratives in order to understand how the social and psychological dimensions relate.